Reciprocating lubricated sliding on textured steel surfaces - Costa,Henara L. (2006)
The presence of a lubricant film between two sliding surfaces reduces adhesion and wear. Engineering surfaces can be textured with a uniform micropattern composed of regularly shaped topographical features, which is expected to improve their lubrication. If the surfaces are sliding against each other with a certain velocity and a lubricant fluid is present in the contact, a hydrodynamic film may form spontaneously between them. In lubricated sliding tests of metallic samples, the two conducting samples can be seen as two conductors separated by a lubricant film, which constitute a capacitor if the two samples are insulated from each other. In this work, a bridge circuit was designed where the capacitor created by the two samples and the lubricant film was one of the components of a bridge. The resistors that compose the bridge were selected in order to provide a large range of linear variation between voltage and capacitance, between approximately 50 and 900 pF and the output was a rectified DC voltage signal corresponding to the average of the resultant AC signal for each film thickness. The apparatus was connected to a reciprocating sliding tester with sinusoidal velocity variation in order to achieve regimes of lubrication varying from boundary to hydrodynamic lubrication over the length of the stroke; the velocity varied between zero at the ends of the stroke and 40 mm s-1 in the middle. Textured samples containing patterns composed of individual circles and lines were tested using this apparatus. The effects of width and percentage of coverage and of feature orientation were analysed. All the results were compared with those from a standard polished surface